Edukasi Kesehatan Gigi dan Mulut: Teknik Menyikat Gigi yang Efektif untuk Anak Sekolah Dasar - Mely Purnadian (Lembaga Pengembangan Kinerja Dosen, 2026)
Dental and oral health is an essential part of overall bodily health. The high prevalence of caries and cavities in children is generally caused by a lack of tooth-brushing skills. Incorrect techniques and improper duration cause food residue to remain, which ultimately triggers the demineralization of the tooth enamel. This socialization activity aims to provide education on the importance of brushing teeth with correct and effective techniques for elementary school students. The activity was conducted at SDIT Al-Azhar Kediri City, using a practical and interactive simulation approach; starting with a PowerPoint presentation, followed by a demonstration of proper tooth-brushing techniques using teaching aids. There were 84 children involved in this activity, and the results showed that approximately 90% of the participants could correctly answer the questions provided. Consequently, this socialization activity successfully increased the participants' knowledge and understanding of maintaining dental and oral health